Impact of Monovalent Counter-ions on the Conformation of Flexible Polyelectrolytes Having Different Molecular Architectures. Issue 25 (11th February 2016) - Chremos, Alexandros; Douglas, Jack F.
ABSTRACT: We explore the impact of monovalent counter-ions on the molecular conformation of highly charged flexible polyelectrolytes for a range of molecular topologies (linear chains, stars, and unknotted and trefoil rings) by molecular dynamics simulations that include an explicit solvent having short range interaction with the polyelectrolyte. In particular, we investigate how the counter-ions near the polyelectrolytes with variable mass influence the average molecular shape. We also characterize the interfacially "bound" counter-ions by calculating the time-averaged number of interfacial counter-ions, as well as the degree to which the polyelectrolytes wrap around the counter-ions by calculating the number of contacts between the counter-ions and the polyelectrolyte.